Administration and Toxicity Profile of the Capizzi Interim Maintenance—Retrospective Study from a Tertiary Care Cancer Centre - Viswanathan, Aarthi; Kumar, Arun; Kaushik, Prakruthi S.; Thumallapalli, Avinash; Ramachandra, C.; Aruna Kumari, B. S.; Appaji, Lingappa; Kumar, Nuthan (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction The Capizzi-style methotrexate (MTX) is an integral part of acute lymphoblastic leukemia (ALL) treatment. The escalating dose of MTX originally used in the United Kingdom and Children’s Oncology Group protocols along with L-asparaginase has been modified in the Indian Childhood Collaborative Leukemia (ICiCLe) group protocol where L-asparaginase has been omitted. The data regarding the incidence of toxicities and ease of administration on the Capizzi-style interim maintenance is not robust.Objectives We have compiled our experience with administration and toxicity profile in children with intermediate-risk ALL.Materials and Methods A retrospective data collection of all children diagnosed with intermediate-risk ALL as per the ICiCLe risk stratification in the year 2019 was included in the analysis. Each cycle of MTX was started after ensuring an absolute neutrophil count of >750/mm3 and transaminases <2 upper limit of normal. As a unit protocol, pre- and post-MTX hydration was administered in all our children. No urine pH or midcycle biochemical parameter monitoring was done. Statistical analysis was done using Microsoft Excel and SPSS version 24 IBM Corp. in Armonk, New York, United States.Results Forty-six children were included in the study. The median age of children in our study was 6 years (range: 1 year 2 months–12 years). Undernutrition was associated with a significant increase in toxicity (p = 0.02). Fifty-two percent of children had evidence of toxicity, elevated transaminases being the most common. There were recurring symptoms resulting in 53 episodes of toxicities overall. Incidence of toxicity was more in the early cycles (<3).Conclusion The pre- and post-MTX hydration is an effective way to reduce toxicities with the Capizzi-style MTX and this course can be administered with ease on outpatient basis with minimal need for monitoring or admission.
Keywords: administration; the Capizzi interim maintenance; toxicity profile